Animal Enchroachment Detection in Croplands using Machine Learning Approaches (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Animal Enchroachment is a major threat to the productivity of the crops, which affects food security and reduces the farmer’s profit. Machine learning-based solutions are used to overcome this problem. Convolu- tional Neural Network (CNN), ResNet-50, and Inception v3 are the three methods used to identify the animals. The proposed model classifies the detected animals and alerts humans through a message to avoid animal intru- sions into properties. Hence, minimising the dangerous consequences caused by the intrusion. The Inception v3 model provides more accurate results compared to the other two models, and it is considered the main method for the proposed model.